School Management Policy Analysis on The Implementation of Inclusion Education in Primary Schools - Amalia, Mutia; Ismail, Ismail; Bahrun, Bahrun; Zakaria, Nurhijrah Binti (Jurnal Ilmu Pendidikan, 2024)
This research investigates school management practices in implementing inclusive education in state elementary schools in Banda Aceh City. Using a qualitative approach with a descriptive research design, the study involved ten subjects: 1 Head of the Elementary School Department of Education and Culture, three principals, three class teachers, and three subject teachers from SD Negeri 1, SD Negeri 24, and SD Negeri 32 in Banda Aceh City. Data were collected through observation, interviews, and documentation and analyzed using qualitative descriptive analysis with data reduction, presentation, and conclusion. The research findings are as follows: 1) Planning for inclusive education in Banda Aceh City public elementary schools needs clear program steps; 2) Implementation of inclusive education has been carried out well, but guidelines are not thoroughly followed due to insufficient resources and program planning; 3) Supervision by principals occurs every three months but is not optimal due to a lack of specific monitoring for inclusive education programs; 4) Evaluation of learning by teachers is periodic but does not align with the principles and criteria for inclusive education assessment; 5) Obstacles include a lack of teacher knowledge about inclusive education, limited school resources, a lack of a specific budget, and insufficient parental understanding in handling children with special needs